Effect of Balancing Exercises on Decreasing Risk of Fall in the Elderly in Desa Baru Kec. Stone Crusher 2019 - Fitriani Fadillah; Desy Mahara (Institute of Computer Science (IOCS), 2020)
Elderly is the last phase in life. Disorders of physical mobility limit the independence of the elderly in fulfilling their daily activities, musculoskeletal disorders are the cause of slowness of movement, and slow response causes the risk of falling in the elderly, so the need for balance exercises. The reduction in the risk of falling can be overcome with balance exercises, namely the berg balance scale. In particular, this study aims to determine the intervention, namely education and balance training given to the elderly against the risk of falling owned by the elderly. This type of research used in this research is to use quantitative, pre-experimental research design with one group pretest - postest design. The sampling technique was purposive sampling, there were 20 elderly people by giving balance training which was measured before and after which was done 2 days a week for 3 weeks using the observation sheet. And analyzed by univariate, bivariate, normality test with Paired sample t-test. The results showed that the majority of the risk of falling was high in the elderly before being given balance training, namely the risk of falling as much as 9 (45.0%), after being given balance training in the elderly, the risk of falling was low as many as 11 people (55.0%), the result of the t test was p = 0.002 (0.005) then Ho is rejected. Ha is accepted, meaning that there is an effect of balance training on reducing the risk of falling with a value of t = 3.621, so there is an effect of balance training on reducing the risk of falling in the elderly as much as 3,621 times. The conclusion is that the effect of balance training on reducing the risk of falling for the elderly in the new village, so that the new village is expected to consider giving balance training to the elderly as an alternative in reducing the risk level of falling in the elderly.